IMPLEMENTATION OF INNOVATIVE LEARNING STRATEGIES TO IMPROVE CHILDREN'S BASIC SKILLS IN RAUDHATUL ATHFAL KARANG JETAK CISAIT, KRAGILAN DISTRICT, IN SERANG REGENCY - Husni, Mohamad; Samsinar, Ade; Nurlelah, Nurlelah; Mardiana, Rani; Izati, Siti Salma Nur; Irawan, Tomi; Amalia, Desta Melani (Yayasan Education and Social Center, 2024)
This community service activity aims to implement innovative learning strategies in Raudhatul Athfal Karang Jetak, Kragilan District, Serang Regency, focusing on improving the basic skills of early childhood. This program has several major components, including teacher training, project-based methods, and educational technology. Teacher training increased their competence in using creative techniques and technology. In contrast, project-based methods and educational technology improved children's fundamental skills such as reading, writing, and arithmetic. The innovative strategies implemented involve the principles of constructivism, multiple intelligence theory, intrinsic motivation, and the use of technology in education. The evaluation findings demonstrate that this method improves kids' learning abilities and engagement pleasantly and efficiently. By following the procedures that have been designed, the quality of the learning process can be continuously enhanced at Raudhatul Athfal Karang Jetak